A new chronometer system to provide real time feedback to swimmers - Perez, P.; Llana, S.; Zahonero, J.; Navarro, P. (First international symposium sciences and practices in swimming, 2006)
In swimming training new directions point to automate the process to give the swimmer and the coach more freedom in the establishment and control of training sessions. This paper describes a new chronometer System that provides feedback in real time and without interfering with the swimmer's execution. The System consists on a leds screen (water resistant) installed on the bottom of the pool, so that swimmers can See it every time they perform a turn. That leds screen can inform about lap times and even text written by the coach. This System can be connected to a PC or PDA, which permits register lap times and provide feedback to swimmers.